Environmentally Responsible Behavior and naturalist intelligence: Biology Learning to Support Sustainability - Istiana, Rita; Sunardi, Oding; Herlani, Fachrine; Ichsan, Ilmi Zajuli; Rogayan Jr, Danilo V.; Rahman, Md. Mehadi; Alamsyah, Mashudi; Marhento, Giry; Ali, Ahmad; Arif, Wiwin Pramita (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2020)
Biology learning needs to support sustainable development. This research was a quantitative-qualitative sequential explanatory mixed research. This research aimed to obtain information about the relationship between naturalist intelligence and environmental responsibility behavior. This research was conducted in February-August 2019. Quantitative research data were obtained by using a questionnaire with a Likert scale for the variables. Qualitative research data were obtained by doing interviews and observations. Quantitative data were analyzed using descriptive statistic calculation. The data hypothesis was tested by using a correlation test with the Product Moment Pearson formula. The result of this research showed that there was a positive relationship between naturalist intelligence and environmentally responsible behavior with regress equation Ŷ = 20.331 + 0,7524X. Correlation coefficient (r) = 0.66 and determination coefficient (r²) = 43.56% meant that the interpretation value was strong. r² value means that 43.56% environmentally responsible behavior correlates by naturalist intelligence and 56.44% environmentally responsible behavior is influenced by other factors. Biology learning must have a role to be able to provide innovations related to increasing students' knowledge about the environment. This study concludes that there is a correlation between the two variables.